If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 4) = (x + -2) Reorder the terms: 5(4 + x) = (x + -2) (4 * 5 + x * 5) = (x + -2) (20 + 5x) = (x + -2) Reorder the terms: 20 + 5x = (-2 + x) Remove parenthesis around (-2 + x) 20 + 5x = -2 + x Solving 20 + 5x = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 20 + 5x + -1x = -2 + x + -1x Combine like terms: 5x + -1x = 4x 20 + 4x = -2 + x + -1x Combine like terms: x + -1x = 0 20 + 4x = -2 + 0 20 + 4x = -2 Add '-20' to each side of the equation. 20 + -20 + 4x = -2 + -20 Combine like terms: 20 + -20 = 0 0 + 4x = -2 + -20 4x = -2 + -20 Combine like terms: -2 + -20 = -22 4x = -22 Divide each side by '4'. x = -5.5 Simplifying x = -5.5
| -(6xy-9)+4(6xy+5)= | | 10(v+2)-4v=2(3v+3)-11 | | 6-3x=5x-10x+12-6 | | 19200=-27x^2+1080x+12312 | | 11m=10 | | c=(-27(9))+(1080(3))+12312 | | 3x^2-27x=30 | | xy+xw=1 | | (-15t^2)+135t-210=0 | | 25x^6-49=0 | | (w^2+2w-15)(8w+16)=0 | | xy+w=1 | | d/3+5=2 | | 3(x+8)=6(y+4) | | C^2+13c=0 | | 2(p^2+4)=7p^2+1 | | 2*(m-5)-7m*(m-5)= | | (9b-6)-4(2b+1)=-5 | | 13-10x=178-5x | | 3(x+2)+1=7 | | 2A=22 | | 13x-2x=70 | | 12-5x=6-7x | | 5x+6x+4+9=3x+5+7x | | 12x-8=124 | | j^2+k^2+jk+k^2+l^2+kl+l^2+j^2+jl=50 | | (4u-5)(4-u)=0 | | -5y+3=-6y+6 | | 0=128t+-16t^2 | | h=128t-16t^2 | | 2x^2+24x-14=0 | | 33-4x=5x+21 |